Review of literature on chronic kidney disease of unknown etiology (CKDu) in Sri Lanka - Noble, A.D.; Amerasinghe, Priyanie H.; Manthrithilake, Herath; Arasalingam, Sutharsiny (International Water Management Institute, 2014)
This manuscript undertakes a review of current published information (peer-reviewed and grey literature) on Chronic Kidney Disease of Unknown Etiology (CKDu) in Sri Lanka. It attempts to provide an overview of the possible environmentally-induced causal factors that have been implicated in the development of the disease, and identifies the gaps in research and recommends potential areas for future research. The review specifically captures the potential role that agriculture and water resources may play as causal factors in the development of the disease, and calls for a systematic approach and stresses the need for an integrated multi-disciplinary research effort to address the problem.